Adsorption capability of heavy metals by chitosan/poly(ethylene oxide)/activated carbon electrospun nanofibrous membrane - Shariful, Md Islam; Sepehr, T.; Mehrali, Mohammad; Ang, Bee Chin; Amalina, Muhammad Afifi (Wiley, 2017)
In this study, activated carbon (AC) was synthesized by chemical activation process from rice husk, with the BET surface area of 2180 m2/g. Chitosan/poly(ethylene oxide) (PEO)/AC nanofibrous membrane (CPANM) was synthesized by electrospinning process. The average fiber diameter was found to be 83 ± 12.5 nm. Incorporation of AC lead to increase in the surface area of CPANM than chitosan/PEO fiber (CPF) by 371 m2/g. X‐ray photoelectron spectroscopy survey and narrow scan analysis further proved the presence of AC in the membrane. CPANM showed higher adsorption capability than CPF. Analysis of the mechanism of heavy metals adsorption by CPANM and CPF hypothesized that, (NH2) is the only active group in CPF, whereas both (NH2) and (COOH) contributed in adsorption for CPANM. Maximum adsorption capacity of CPANM for Cr(VI), Fe(III), Cu(II), Zn(II), and Pb(II) ion was found to be 261.1, 217.4, 195.3, 186.2, and 176.9 mg g−1 respectively.